2008
DOI: 10.1007/s12032-008-9055-1
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of single agent docetaxel in patients with platinum-refractory non-small cell lung carcinoma

Abstract: Second-line chemotherapy with single-agent docetaxel offers a small but significant survival advantage with acceptable toxicity for patients with advanced NSCLC who have platinum-refractory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The PR rate with docetaxel was 15 % while no cilengitide-treated patient had a PR. The PR rate with docetaxel seen in this study is similar to the 13–22 % rates reported in other monotherapy studies of the taxane in advanced NSCLC [2527]. …”
Section: Discussionsupporting
confidence: 89%
“…The PR rate with docetaxel was 15 % while no cilengitide-treated patient had a PR. The PR rate with docetaxel seen in this study is similar to the 13–22 % rates reported in other monotherapy studies of the taxane in advanced NSCLC [2527]. …”
Section: Discussionsupporting
confidence: 89%
“…Chemotherapy is a significant component of current first-line treatment for LAD patients. Docetaxel, a semisynthetic analogue of paclitaxel, is widely used in the treatment of LAD with genotoxic effects attributed to the induction of apoptosis and cell cycle arrest [3]. However, chemoresistance remains a major impediment to clinical application of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of significant achievement in the treatment of LAD over the last decade, the prognosis for patients with advanced disease remains poor [2]. Docetaxel, a semi-synthetic analog of paclitaxel, was granted approval as a first-line chemotherapy regimen for NSCLC [3]. However, chemoresistance remains a major obstacle constraining the clinical application of this agent.…”
Section: Introductionmentioning
confidence: 99%